Leadership in Islamic Boarding Schools and the Formation of Student Discipline Character: A Qualitative Analytical Study Using NVivo 15 Plus - Nuris Noviannisa Maghfirahmi; Niswanto; Suparta Rasyid (Lembaga Bale Literasi, 2026)
This study aims to analyze the planning, implementation, and challenges of Islamic boarding school leadership in improving student discipline at MTsT and MAT Daarut Tahfizh Al-Ikhlas Banda Aceh. Disciplinary problems including tardiness at congregational prayers, absenteeism from tahfizh sessions, and schedule inconsistency indicate the critical need for systematic leadership in fostering student discipline. Qualitative descriptive approach was employed, data were collected through in depth interviews, observations, and document analysis from 15 purposively selected participants comprising the Deputy Director, dormitory supervisors (Musrif/Musyrifah), teachers, and students. Data were analyzed using NVivo 15 software through open, axial, and selective coding. Findings reveal three key dimensions; First, discipline planning was conducted participatively through deliberative forums involving all pesantren components, with rule making as the most dominant node; task distribution was implemented through a three session shift system ensuring 24 hour supervision; Second, leadership implementation proceeded in an integrated manner with role modeling as the primary strategy, supported by layered supervision, intensive coordination, personalized approaches, and educationally grounded reward and punishment mechanisms. The last challenges were multidimensional, encompassing inadequate physical facilities, dense activity schedules, recurring violations, peer influence, and differing characteristics between MTsT and MAT students. Pesantren leadership has functioned adaptively in alignment with Islamic values; however, infrastructure development, schedule restructuring, and broader teacher participation in strategic planning require further improvement